Anthropology as an Approach in Islamic Studies - Nandra Arif Fani, Mauliya (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
God sent down revelation as a means of guiding the life of mankind. Revelation is gathered in the form of religion that provides harmony in human life. This research is a research with qualitative methods and uses a descriptive approach. This research uses relevant books and articles in collecting data so that this research is a literature research with references to articles of various relevant journals as a primary data source. Anthropology is a term that is no less interesting in the world of research. The word derived from the Greek anthropos means man and logos which means science. So, it can literally be argued that anthology is a science that studies humans. Religion has an existence that is never detached from the social reality that surrounds it. Religion is a cultural phenomenon, in which the religious practices that arise in a society are the result of understanding the doctrine of the teachings of the religion itself. As a scientific discipline, the anthropological approach has characteristics. Among the characteristics in the modern anthropological approach is holism, that is, the view that social practices should be researched in context and essentially seen as related practices in those societies. The area of anthropology is limited only to the study of emerging phenomena. The study or study of religion with an anthropological approach seeks to study about humans and society related to religion and culture that develops in that society. In other words, religious anthropology examines the relationship between man and supernatural power, human thought, attitudes and behavior in relation to unreal power.